IMPLEMENTATION OF DANISH SEINE PROHIBITION POLICY IN BATANG REGENCY OF CENTRAL JAVA PROVINCE, INDONESIA - Ravanelli R.; Fitri A.D.P.; Mudzakir A.K. (Russian Journal of Agricultural and Socio-Economic Sciences, 2021)
Danish seine (Cantrang) is a controversial fishing gear caused by it considered as destructive fishing and has a low level of selectivity. A policy regulation on the prohibition of using Cantrang as fishing gear in Indonesia has been issued through the Ministry of Marine Affairs and Fisheries Number 2 of 2015 with the aim of preserving demersal fish resources especially in the Fisheries Management Area of the Republic of Indonesia (WPP-RI) 712. However, this policy has created opposition from Cantrang fishermen due to the economic impact, causing fishermen lost their only source of livelihood. This study aims to analyze the policy implementation factors that influence the implementation of the Cantrang prohibition policy. This study used a descriptive method with a qualitative approach with policy outputs and policy outcomes as indicators. Based on the results, outputs indicators and outcomes indicators in the implementation of the Cantrang prohibition policy was not achieved, especially the long-term outcome that became the policy objectives, which are to maintain the sustainability of demersal fish resources, to preserve coral reefs ecosystem and to manage illegal fishing activities for using non-environmentally friendly fishing gear are failed to be implemented. Factors that influence the failure of the Cantrang prohibition policy implementation are government’s inconsistencies, disposition of fishermen as the policy target, and lack of financial support towards fishing gear replacement.